Proportion of colonic carcinoma in cases presenting with acute intestinal obstruction: a cross sectional study - Joseph, Pauly T.; Thomas, Rajiv Sajan; V., Sutharjivel (International Surgery Journal, 2021)
Background: Acute intestinal obstruction is one of the most common emergencies encountered by the general surgeon in routine practice. Although historically, obstructed hernia has been the most common cause, recent studies have shown that adhesive intestinal obstruction is now the commonest reason. Malignant bowel obstruction is also on the rise especially with the change in dietary habits. This study aims at identifying the proportion of colonic carcinoma in cases presenting with acute intestinal obstruction. Methods: The patients with acute intestinal obstruction which was diagnosed clinically and radiologically were studied. Based on operative and clinical findings along with investigation results, the etiology was identified. The patients having colonic neoplasms were identified and the data was compared with other etiological factors to find out the proportion of colonic carcinoma in the cases. Results: The proportion of colon cancer in patients presenting with acute intestinal obstruction was around 15%. The most common cause was obstructed hernia followed by post-operative adhesions. Males were more commonly affected than females. Most of the cases underwent operative management. The most common age group affected was around 50-60 years. Conclusions: This study confirms that there is a definite rise in the number of cases of colon cancer presenting as acute intestinal obstruction. There is also a skewing of the age at presentation towards younger age groups. Small bowel obstructions were much more common mainly due to adhesions and obstructed herniae.